PERLINDUNGAN KREDITOR KONKUREN DALAM HUKUM KEPAILITAN - Rai Mantili; Putu Eka Trisna Dewi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Ngurah Rai, 2020)
Bankruptcy is the last way to solve the debt problem between debtors and creditors. The role of bankruptcy institutions is basically very important to ensure that both debtors and creditors receive justice from the bankruptcy process. In bankruptcy, concurrent creditors such as suppliers (small entrepreneurs) often do not get payment from the debts of the bankrupt debtors. This is because the bankruptcy bill is not sufficient to be shared with creditors. This research is a law research using literature study. The position of a concurrent creditor who is the last creditor whose debt is guaranteed to be repaid from the bankruptcy bill needs attention regarding legal protection in the bankruptcy process